Use of home pregnancy tests among adolescent women. - Sadler, Lois S; Dynes, Michelle W; Daley, Alison M; Ickovics, Jeannette R; Leventhal, John M; Reynolds, Heather (MCN. The American journal of maternal child nursing, 2004)
Many adolescents use home pregnancy tests when they suspect pregnancy. However, because of developmental issues and greater variation in menstrual cycles, teens are at risk for obtaining false-negative test results. Moreover, with teens, the need for a pregnancy test often accompanies the need for comprehensive reproductive care including evaluation for sexually transmitted infections and contraception. This article reviews the mechanisms of home pregnancy testing including sensitivity, accuracy, and home testing procedures. Clinical strategies for improving the accuracy of home pregnancy tests for teen users are discussed. Lastly, policy implications to improve teens' access to more accurate pregnancy testing and to reproductive health services are suggested.
Keywords: Adolescent; Adolescent Behavior; Female; Humans; Maternal-Child Nursing; Practice Guidelines as Topic; Pregnancy; Pregnancy in Adolescence; Pregnancy Tests; Self Care; Sex Education